Estimasi Penyebaran Sedimen Cekungan Jawa Timur Dengan Metode Gravity - Adib Hasan, Muhamad; Nurwidyanto, M. Irham (BERKALA FISIKA, 2008)
This research is a reconnaissance study to predict the distribution and depth of the sediment basin in East Java based on Bouger Anomaly data in gravity method.Bouger anomaly is projected to flat plane used by equivalent point mass source method. Upward continuation is used to separate the regional and residual anomaly.Â  Modeling sub surface in two dimensions are used by polygon Talwani method by help computer program Geomodel.The results of this research can be concluded that in East Java sediment basin has about 6 km in depth. The central basin are reside in mid of East Java, there are around Sragen, Karanganyar, Ngawi, Madiun, Nganjuk, Kediri, Bojonegoro, Jombang and Mojokerto which in the east west direction. In the eastern part of East Java Basin there are Sidoarjo, Pasuruhan, Probolinggo and Maura bay has direction in northwest to southeast. Key words: Basin, basement, sediment, Bouger Anomaly